Andrey Kiselev: the Life and the Legend - KARP, ALEXANDER (Educação Matemática Pesquisa Revista do Programa de Estudos Pós-Graduados em Educação Matemática, 2012)
Abstract This article is devoted to Andrey Kiselev, probably the most well-known Russian author of mathematics textbooks. His books remained in schools for nearly one hundred years, and his name became legendary, symbolizing the “good old days” when all was supposedly well with mathematics education. Meanwhile, even in Russia, let alone abroad, many aspects of Kiselev’s life are little known. Their study facilitates a better understanding of the complicated nature of the development of Russian and Soviet mathematics education, including the connection between them and seemingly distant social-political issues. The present article undertakes such a study. The author draws on his Russian publications, materials from Russian archives, and other primary sources. Resumo Este artigo trata de Andrey Kiselev, provavelmente o mais conhecido autor russo de livros didáticos de matemática. Seus livros permaneceram nas escolas por quase cem anos, e seu nome tornou-se uma lenda, denotando os “bons velhos tempos” quando tudo parecia estar bem com a educação matemática. Entretanto, mesmo na Rússia, e muito menos no exterior, muitos aspectos da vida de Kiselev não são bem conhecidos. O estudo desses aspectos ajuda a compreender a natureza complexa do desenvolvimento da educação matemática russa e soviética, inclusive suas relações e as aparentes questões sócio-políticas distantes. Este artigo apresenta tal estudo baseando-se em suas publicações em russo, materiais encontrados em arquivos da Rússia e outras fontes primárias.